God's word alone : the authority of scripture : what the reformers taught...and why it still matters - Barrett, Matthew, 1982- (2016)
Historians and theologians alike have long recognized that at the heart of the sixteenth-century Protestant Reformation were five declarations (or "solas") that distinguished the movement from other expressions of the Christian faith. Five hundred years later, we live in a different time with fresh challenges to our faith. Yet these rallying cries of the Reformation continue to speak to us, addressing a wide range of contemporary issues. The Five Solas series will help you understand the historical and biblical context of the five solas and how to live out the relevance of Reformation theology today. In God's Word Alone$1 (BThe Authority of Scripture, scholar and pastor Matthew Barrett looks at the historical and biblical roots of the doctrine that Scripture alone is the final and decisive authority for God's people. He examines the development of this theme in the Reformation and traces the crisis that followed resulting in a shift away from the authority of Scripture. Barrett shows that we need to recover a robust doctrine of Scripture's authority in the face of today's challenges and why a solid doctrinal foundation built on God's Word is the best hope for the future of the church.--Publishers
Sola scriptura -- God's word under fire, yesterday and today -- The road to reformation: biblical authority in the sixteenth century -- The modern shift in authority: the enlightenment, liberalism, and liberalism's nemeses -- Today's crisis over biblical authority: evangelicalism's apologetic and the postmodern turn -- God's word in redemptive history -- God's word in the economy of the gospel: covenant, trinity, and the necessity of a saving word -- God speaks covenantal words: creation, fall, and the longing for a better word -- God's covenantal word proves true: Christ, the word made flesh -- The character of God's word and contemporary challenges -- God speaks with authority: the inspiration of scripture -- God speaks truthfully: the inerrancy of scripture -- God speaks to be heard: the clarity of scripture -- God's speech is enough: the sufficiency of scripture -- Always reforming according to the word of God.
Includes bibliographical references (pages 375-388) and indexes.
Keywords: Bible -- Evidences, authority, etc; Reformed Church -- Doctrines